Papua New Guinea food price bulletin: January 2024 - International Food Policy Research Institute; Kedir Jemal, Mekamu; Schmidt, Emily (International Food Policy Research Institute, 2024)
This bulletin presents food price trends during the fourth quarter of 2023 and compares current prices with those of previous years (2021-2022) from major markets across Papua New Guinea using data collected by Fresh Produce Development Agency (FPD). It is important to note that during the fourth quarter of 2023, none of the markets had a complete set of fortnightly price data. While Port Moresby had fortnightly observations for October and December, the rest of the markets (Goroka, Banz Kokopo, Lae) collected price data on a monthly basis. No data was collected in the 4th quarter from Mt Hagen market. To access the complete and comprehensive price dataset, you can download it from our website. This bulletin reports the average real monthly fresh food price data from Port Moresby, Goroka, Banz, and Kokopo markets. The prices presented in this report are in real terms, adjusted for inflation using FAO consumer price index (CPI).